2001
DOI: 10.1002/bit.1086
|View full text |Cite
|
Sign up to set email alerts
|

Engineering temperature‐sensitive poly(N‐isopropylacrylamide) polymers as carriers of therapeutic proteins

Abstract: This study was carried out to engineer N-isopropylacrylamide (NiPAM) polymers that contain protein-reactive N-acryloxysuccinimide (NASI) and hydrophobic alkylmethacrylates (AMAs). These thermoreversible, protein-conjugating polymers hold potential for retention of therapeutic proteins at an application site where tissue regeneration is desired. The lower critical solution temperatures (LCST) of the polymers were effectively controlled by the AMA mole content. The AMAs with longer side-chains were more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 41 publications
6
63
0
Order By: Relevance
“…The shift in the cloud-point of poly(NIPAM) is based on the balance between the hydrophilic and hydrophobic groups on the polymer backbone. Similar changes in cloud-points were shown by other works introducing hydrophilic or hydrophobic moieties in the poly(NIPAM) backbone (Takei et al, 1993;Brazel and Peppas, 1995;Kumar et al, 1998;Homan, 2000;Uludag et al, 2001). If the NIPAM monomer is copolymerized with more hydrophilic monomers such as acrylamide, the LCST increases and may even disappear.…”
Section: Results and Discussion Preparation And Characterization Of Asupporting
confidence: 68%
“…The shift in the cloud-point of poly(NIPAM) is based on the balance between the hydrophilic and hydrophobic groups on the polymer backbone. Similar changes in cloud-points were shown by other works introducing hydrophilic or hydrophobic moieties in the poly(NIPAM) backbone (Takei et al, 1993;Brazel and Peppas, 1995;Kumar et al, 1998;Homan, 2000;Uludag et al, 2001). If the NIPAM monomer is copolymerized with more hydrophilic monomers such as acrylamide, the LCST increases and may even disappear.…”
Section: Results and Discussion Preparation And Characterization Of Asupporting
confidence: 68%
“…A close relationship between the physicochemical properties of the polymers and the protein retention was established. Lowering the LCST of NiPAM polymers (from $27 o C for the homopolymer to <20 o C) by incorporating hydrophobic monomers resulted in better entrapment of proteins with increased protein localization at an injection site [13]. Incorporating protein-reactive NASI groups into the polymers resulted in protein conjugation to polymers, which increased the retention of proteins and reduced their burst release [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies from this group have focused on the use of NiPAM-based thermoreversible polymers to localize morphogenetic proteins at a desired anatomical site [12,13]. The morphogenetic proteins are de novo tissue inducers whose activity depends on the local retention of the proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An optimized delivery system might improve the osteoinduction of the device, while reducing the loading amount of BMP as much as possible, which offers double advantages of being safer as well as less expensive 3) . Several reports indicated that too rapid release of BMP-2 decreased osteoinduction while high retention of BMP-2 elicited more bone formation 4,5) . It is likely that an extremely low dose of BMP-2 is enough to enhance osteoinduction if BMP-2 is appropriately delivered to the site of action 6) .…”
Section: Introductionmentioning
confidence: 99%